Millenial Purchasing Trends in Islamic Fashion : A Comparative Analysis of Malaysia and Indonesia - Siti Ifa Nurjannah; Nikmatul Masruroh; Hersa Farida Qoriani (The Eastasouth Management and Business, 2026)
The growth of the islamic fashion industry in Southeast Asia, Particulary in Malaysia and Indonesia, reveals unique consumption dynamics among Muslim millenial. The rise of social media has accelerated the transformation of islamic fashion, blending eligious values with popular culture and digital aesthetics. This study aims to: (1) analyze differences in style preferences of Muslim millennials in Malaysia and Indonesia; (2) identify representations of Islamic values in fashion-related social media content; and (3) examine the use of different social media platforms as spaces for expressing and consuming Islamic fashion. Employing a library research approach with Thematic Content Analysis (TCA), data were collected from 20 social media posts each from TikTok and Instagram in both countries. Using Habermas’ critical analysis, the findings show that Indonesian millennials favor casual and urban styles influenced by K-pop and streetwear, while Malaysian millennials prefer traditional-modern aesthetics such as tudung labuh and baju kurung. Islamic narratives in Indonesia are conveyed through religious captions, whereas in Malaysia they are expressed visually through modest and covered fashion. TikTok dominates in Indonesia, while Instagram prevails in Malaysia due to its curated visual appeal.